Heterozygous variant in FGFR3 underlying severe phenotypes in the second trimester: a case report - Shujun Chen; Hongmei Dong; Yong Luo; Yingpin Zhang; Pan Li (BMC, 2023)
Abstract Background Achondroplasia is a congenital skeletal system malformation caused by missense variant of FGFR3 gene with an incidence of 1 per 20,000-30,000 newborns, which is an autosomal dominant inheritance disease. Despite similar imaging features, the homozygous achondroplasia is absolutely lethal due to thoracic stenosis, whereas heterozygous achondroplasia does not lead to fetal death. Case presentation A fetus with progressive rhizomelic short limbs and overt narrow chest was detected by prenatal ultrasound in the second trimester. Gene sequencing results of amniotic fluid sample indicated a rare missense variant NM_000142.4: c.1123G > T(p.Gly375Cys), leading to a glycine to cysteine substitution. Re-sequencing confirmed that it was a heterozygous variant, and thoracic stenosis was then confirmed in the corpse by radiological examination. Conclusions We identified a heterozygous variant of the FGFR3 gene as the rare pathogenic variant of severe achondroplasia in a fetus. Heterozygous variants of p.Gly375Cys may have a severe phenotype similar to homozygote. It's crucial to combine prenatal ultrasound with genetic examination to differentiate heterozygous from homozygous achondroplasia. The p.Gly375Cys variant of FGFR3 gene may serve as a vital target for the diagnosis of severe achondroplasia.